Antimalassezia Activity of Medicated Antidandruff Shampoo Formulated with Microwave Dried Garlic Powder with Improved Allicin Stability - Gitanjali, Deokar; Prajakta, Pethkar; Swati, Bakshe; Kiran, Erande; Rajendra, Bhambar (Natural Products Journal, The, 2014)
Dandruff is a very common non- inflammatory scalp condition caused by lipophilic, dimorphic yeast malassezia furfur. Garlic (Allium Sativum, Liliacae) contains allicin which is its potential principle constitutent that posses antiviral, antifungal, and parasitic activity. Content of allicin in microwave assisted garlic powder and aqueous garlic extract was found to be 1242.29 μg/gm of garlic powder and 552.26 μg/gm of garlic bulbs respectively by Solid phase extraction–UV method. Minimum inhibitory concentrations of microwave assisted garlic powder and aqueous garlic extract was found to be 268.33 μg /ml and 249.6 μg /ml respectively. From the minimum inhibitory concentration (MIC) obtained, the microwave assisted garlic powder and aqueous garlic extract were then incorporated at different percentages into shampoo formulations. The shampoo formulations were evaluated for two months at room temperature and 4°C. Aqueous extract containing shampoo showed inhibitory action for 1 week (7 days) but growth was observed after 2 weeks(14 days) at both temperature conditions. Microwave assisted garlic powder containing shampoo when kept at 4°C showed inhibitory action up to 4 weeks (28 days) but growth was observed after 5 weeks (35 days) and shampoo formulations kept at room temperature showed inhibitory action up to 5 weeks(35 days) but growth was observed after 6 weeks(42days). Study shows that microwave drying technique helps in improving stability of allicin. Whereas Storage at refrigerator temperature has no role in stability improvement of allicin in the formulation.
Keywords: malassezia furfur